Pengembangan Alat Peraga Viskositas Berbasis Mikrokontroler untuk Meningkatkan Penguasaan Konsep Fisika (UPEJ Unnes Physics Education Journal, 2022)
This study aimed to develop a viscosity teaching aid based on microcontroller to improve mastery of physics concept. The researched method used the research and development method with the subject of research was 28 students which grade XI semester of State Senior High School 1 Grabag 2020/2021 academic year. This researched began with the development of a viscosity teaching aid based on microcontroller along with its guide book and then implemented with a demonstration method to determine students mastery of the viscosity concept. The instruments used included teaching aids, test, and questionnaire sheets. The data analyzed was a form of results of the calibration test of the props, the feasibility test questionnaire by the expert validator and the results of the application in learning included cognitive domains in the form of pretest and postest. The results showed that the teaching aid had gone through a calibration test with an accuracy percentage of 88,855%, while based on a feasibility test by an expert validator regarding the feasibility test of teaching aids, the percentage was 95,83%, which means it was very feasible and the guide book was 87,92% which means it is very feasible. The implementation of a viscosity props can improve the mastery of student’s viscosity concept with n-gain values reaching 0.497 (medium criteria).